Predictors of Paid Employment Status Among Individuals With Spinal Cord Injury in South Korea: An Exploratory Study Using Random Forest Analysis - Kyungah Song; Jincheol Lim; Onyoo Kim (Annals of Rehabilitation Medicine, 2026)
Objective: To explore factors affecting the paid employment of individuals with spinal cord injury (SCI) in South Korea.Methods: Data collected from previously and currently community-dwelling adults with SCI (n=538) who responded to the 125-item self-reported International Spinal Cord Injury Survey questionnaire were analyzed using random forest and decision tree modeling.Results: In total, 75.1% responders were male, 53.9% were unmarried, 90.1% lived with family, and 84.8% received daily living assistance; the most frequent education level was high school or below (56.1%), and the percentage of participants with paraplegia and complete injuries was 57.2% and 58.7%, respectively. Average age and mean SCI duration were 46.31 and 15.25 years, respectively. Factors with a positive effect on engaging in paid employment included greater total monthly household income, younger age, higher self-efficacy, better quality of life and satisfaction, access to vocational rehabilitation services, absence of disability benefits, no need for daily living assistance, greater independence, no difficulties engaging in activities, absence of sleep disturbances, higher education level, and being unmarried.Conclusion: Employing the random forest method and a large dataset, we identified key predictors of paid employment, corroborating previous findings and establishing a foundation for policy development for employment opportunities.